2011
DOI: 10.3109/01913123.2011.553351
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Innervation of the Female Human Umbilical Skin: Morphological Studies

Abstract: The umbilical skin of females has abundant sensory innervation similar to that of the glans penis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In a study of innervations of the umbilical skin, authors are quoted to have found epidermal and dermal numerous tactile cells and corpuscles, and abundant end-bulblike genital structures. Nerve bundles were observed together with bulbous and lamellar corpuscles with abundant nerve endings both in the papillary and reticular dermis ( 18 ).…”
Section: Differences In Umbilical and Vaginal Innervationsmentioning
confidence: 99%
“…In a study of innervations of the umbilical skin, authors are quoted to have found epidermal and dermal numerous tactile cells and corpuscles, and abundant end-bulblike genital structures. Nerve bundles were observed together with bulbous and lamellar corpuscles with abundant nerve endings both in the papillary and reticular dermis ( 18 ).…”
Section: Differences In Umbilical and Vaginal Innervationsmentioning
confidence: 99%
“…[12][13][14] Research has shown that there is relatively dense sensory innervation in the umbilicus, comparable to that in the lips and external genitalia. 15 On the contrary, the TLDG_ P group showed higher NRS scores and more analgesic usage than the TLDG_U group. In the Pfannenstiel incision, innervating nerves of the suprapubic area and lower abdomen, such as branches of the iliohypogastric or ilioinguinal nerves are easily damaged.…”
Section: Discussionmentioning
confidence: 89%
“…The vaginal nerves are mainly concentrated in the anterior and distal vaginal walls, while the nerves in the posterior vaginal fornix are sparse, and the vaginal nociceptive nerves are not sensitive. The umbilical area has more nerve endings and sensory innervation, which makes it more sensitive than other vaginal areas [19][20][21]. A recent study byYang et al showed no difference in VAS scores between vNOTES hysterectomy and single-port LAVH at 12 and 24 h after surgery 5.…”
mentioning
confidence: 99%